Postharvest characterization and chemical composition of sweet potato (Ipomoea batatas (L.) Lamb.) Topera variety. - García-Méndez, Auris Damely (2016)
The objective of this work was to characterize the chemical composition and the postharvest quality of sweet potato Topera variety from a semi-mechanized production with Good Agricultural Practices (GAP). The study was conducted at the Laboratory of Primary Processing of Agricultural Products and Food Biochemistry of the Faculty of Agronomy (FAGRO) at the Central University of Venezuela (UCV) in 2014. The methodology allowed to determine some physical and textural characteristics, as well as the chemical composition using the AOAC methods (Association of Official Analytical Chemists). Sweet potatoes with a lower coefficient of weight variability (CV: 20.12%), form (CV: 5.63%), and size (CV: 12.80%) were obtained. This response allowed to establish three categories of quality with a low incidence of defects (2.15%) and physical-mechanical damage (30.25%), the latter is associated to the high resistance of the material (6.25+0.05 Kgf/mm). Sweet potatoes presented 9.88% of reducing sugars, 6.19% fiber, and 4.13% of protein; these nutritional characteristics suggest its use as a food supplement. The semi-mechanized production with the implementation of the BPA techniques allowed to obtain sweet potatoes with important features for the food processing agribusiness IV Gama and, at the level of the consumer, with a homogeneous physical quality.